A 20-Year Journey Through an Orphan African Baobab (Adansonia digitata L.) Towards Improved Food and Nutrition Security in Africa - Assogbadjo, Achille E.; Chadare, Flora Josiane; Manda, Leonard; Sinsin, Brice (Frontiers in Sustainable Food Systems, 2021)
The African baobab (Adansonia digitata L.) is a multipurpose orphan tree species of the semi-arid and sub-humid Sub-Saharan Africa where it plays an important role in rural livelihoods. Its wide distribution and dense nutrition properties make it an important species for food and nutrition security in Africa. However, despite the increasing interest in the species over the past two decades, the full potential of baobab remains underexploited. This review highlights strides made over the past 20 years (2001–2020) towards harnessing and unlocking the potential values of baobab in Benin, West Africa, to contribute to food and nutrition security. Challenges and threats are identified, and next steps suggested to guide research and development initiatives for orphan tree fruit species like baobab to address hunger and malnutrition in Africa.